(untitled) (Asian Education Studies, 2022)
Based on the basic concept of engineering education professional certification student center, achievement orientation, continuous improvement, in view of the current situation of poor writing ability of undergraduate scientific and technological thesis, weak scientific research consciousness, combined with the graduation requirements from the syllabus, course content, teaching methods, assessment methods and other aspects of the reform. The reform has played a beneficial help to improve students’ subjective initiative in learning, cultivate teamwork spirit, and vacation to the understanding of scientific and technological papers and writing ability. The results can also provide a useful reference for the curriculum teaching reform under the background of other engineering education professional certification.